בין תהום לעיוורון: תיאולוגיה פוליטית וחילון העברית אצל גרשם שלום וח"נ ביאליק - צמיר חמוטל (מכאן, 2014)
The article examines Gershom Scholem’s famous letter to Franz Rozenzweig, “Confession on the Subject of our Language” (1926) and H.N. Bialik’s essay, “Revealment and Concealment in Language” (1916) in relation to one another, as two different responses to the Zionist project of secularizing Hebrew into a spoken language. The major argument is that Bialik’s essay, usually read as referring to the question of whether language in general is capable of representing reality, needs in fact to be read in relation to the historical and cultural context of its time – i.e., the particular Hebrew language in the particular time and place of the crystallization of Zionist culture. Reading this essay in detail reveals Bialik’s complex and conflicting position in relation to the secularization of Hebrew, and can be viewed to some extent as a tragic confession about his own silence as a poet.